Introverted and Extroverted English Department Students in Classroom Interaction - Akifah, Firyal Hasna; Hayati, Rizka (IKIP Siliwangi, 2025)
This study explores how personality types student engagement in classroom interaction during English language learning. It focuses on identifying differences in participation between introverted and extroverted students, as well as examining the types of responses they demonstrate. The research employs a descriptive qualitative method using classroom observation and a personality test based on the Myers-Briggs Type Indicator (MBTI) to classify students into personality categories. The study was conducted among sixth-semester English education students at Pekalongan University, involving 18 participants, including 10 extroverts and 8 introverts. Findings reveal that extroverted students tend to participate more actively in verbal activities such as discussions and presentations. They exhibit strong behavioral and affective responses, including confidence, enthusiasm, and verbal interaction. In contrast, introverted students are more reserved, often avoiding direct verbal interaction, yet displaying cognitive engagement through listening and internal processing. Social dynamics also affect their interaction patterns, both types prefer interacting within familiar peer groups, and comfort levels influence their willingness to participate. These findings suggest the importance of responsive teaching strategies that accommodate different personality traits, ensuring that all learners can meaningfully engage in classroom activities and develop their communication skills in supportive environments.